The influence of team reflexivity on employee’s feedback-seeking behavior: a multi-level perspective - Liu, Mengli; Liu, Bing; Sun, Qihui; Wang, Huijuan; Zhang, Yixin (Frontiers in Psychology, 2025)
The dynamism and uncertainty of the work environment increasingly emphasize the importance of employee’s feedback-seeking behavior. Based on transactive memory system theory, the current study explores the multi-level effect of team reflexivity on team member’s feedback-seeking behavior. Survey data collected from 197 participants in 56 teams in China showed that team reflexivity had a positive indirect effect on team member’s feedback-seeking behavior, and team transactive memory system (TMS) mediated such effect. In addition, results also indicated that team shared mental models (SMMs) moderated the effect of team reflexivity on TMS. The research findings can help organizations recognize the importance of team reflexivity, TMS, and SMMs in promoting employees’ feedback-seeking behavior. Based on this understanding, organizations can better formulate strategies to leverage team reflexivity, TMS, and SMMs to enhance team member’s feedback-seeking behavior, which will also be beneficial for the sustainable development of the organization.